A percepção de saúde em idosos com doença de Parkinson praticante da caminhada nórdica - Ignácio, Erim Andressa de Oliveira (2020)
Introduction: Aging can have consequences such as degenerative diseases such as Parkinson's disease, which has its own physical changes, in addition to leading the elderly to a negative self-assessment of health. Objective: to analyze the perception of health in patients with Parkinson's disease who practice Nordic walking. Method: A sample composed of 13 elderly people aged 60 years or older, participating in the Nordic Walking project of ESEFID - School of Physical Education, Physiotherapy and Dance, of the Federal University of Rio Grande do Sul was chosen. The volunteers answered a questionnaire of perception of health and were evaluated posturally by the flexicurve method. The data were analyzed using a comparative table between the male and female genders with the variables of standard and off-standard kyphosis and positive and negative self-assessment. Results: showed that 15.4% of the volunteers had non-standard kyphosis, and when interviewed about their perception of health, 53.85% of the volunteers evaluated themselves positively. Conclusion: The perception of the elderly's current health was positive.